AN ILLOCUTIONARY AND PERLOCUTIONARY STUDY OF SHERLOCK HOLMES IN ENOLA HOLMES 2 - Rochmah, Maulidya; Suhandoko, Suhandoko; Rosyidah, Nur; Syuhra, Marsha Aqillah Putri (Universitas PGRI Sumatera Barat, 2024)
This study aims to examine the illocutionary acts used by the secondary character, Sherlock Holmes, in the movie Enola Holmes 2. Using a descriptive qualitative method, the study analyzed the dialogue in the movie transcript to identify the types of illocutionary acts employed by the characters. The study found that all types of illocutionary acts proposed by Searle (1969) were present in the movie. The most frequently used illocutionary act by Sherlock Holmes was assertive (55.2%), which reflects his role as a professional detective who delivers information and updates on his cases. In contrast, commissive (4.6%) was the least used illocutionary act by Sherlock Holmes, as he rarely makes promises to other characters. The study also examined the perlocutionary acts, which indicate the response of the interlocutors to the illocutionary acts used by Sherlock Holmes. The responses ranged from irritation to persuasion, encouragement, and sadness. This study highlights the importance of understanding the use of illocutionary acts in effective communication and provides insight into the language of a well-known literary character.